The effectiveness of community share ownership trusts on community development: the case of Mhondoro Ngezi district from 2012 to 2017 - Chimutenga, Rumbidzai (Midlands State University, 2019)
CSOTs were established in order to empower the indigenous rural people who have been historically disadvantage from the national development. Therefore, the study seeks to analyse the effectiveness of Community Share Ownership Trust towards developing the communities. The study centres on the objectives of finding out the role of CSOT in promoting community development, community participation in the decision making, the effectiveness of CSOTs engagement in rural development from 2012 to 2017 and the challenges that are affecting the operation of CSOT in promoting community development. The researcher employed the use of both qualitative and quantitative as way of collecting data. Questionnaires, observation and interviews were, also used as research instrument in order to attain reliable information. The findings from the research pointed that, the CSOT has empowered the community of the Mhondoro-Ngezi through income generating and social projects which have improved the living standards. On the other hand, the CSOT developmental progress is hindered by political interference and lack of expertise of board members. The researcher recommends that, community programmes should benefit everyone regardless of been a political party member. The scheme is viable for local development but there is need to overcome challenges.